A mediation system to facilitate cooperation in a co-design platform - Fougères, Alain-Jérôme; Ospina, Victoria Eugenia (IEEE Xplore, 2011)
We present a mediation system, developed to give support to participants in mechanical-system-designer activities. Sufficient assistance is needed to facilitate and coordinate actors' activities. To accomplish this goal we introduce an artificial actor: Mediator. Mediator takes part to collaborative activity, with a specific role of facilitating cooperation between designers. This role of assistance, differentiate Mediator from other actors. This one is endowed with specific skills of cooperation (communication; awareness, coordination, co-memorization), requiring some acquired knowledge, which allow them to give assistance to human actors. We will define the types of knowledge defined for our proposed mediation system. Then we will illustrate the use of memorized knowledge by Mediator during an instrumented activity of technical functional analysis.

Presentamos un sistema de mediación, desarrollado para dar apoyo a los participantes en actividades de diseño de sistemas mecánicos. Se necesita asistencia suficiente para facilitar y coordinar las actividades de los actores. Para lograr este objetivo introducimos un actor artificial: Mediador. El mediador participa en la actividad colaborativa, con el papel específico de facilitar la cooperación entre diseñadores. Este papel de asistencia, diferencia al Mediador de otros actores. Éste está dotado de habilidades específicas de cooperación (comunicación, sensibilización, coordinación, comorización), que requieren de unos conocimientos adquiridos, que le permitan prestar asistencia a los actores humanos. Definiremos los tipos de conocimiento definidos para nuestro sistema de mediación propuesto. Luego ilustraremos el uso del conocimiento memorizado por Mediator durante una actividad instrumentada de análisis funcional técnico.
Keywords: cooperative systems; functional analysis; groupware; software agents; Sistemas cooperativos; Análisis funcional; Trabajo en grupo; Agentes de software; Sistema de mediación; Trabajo colaborativo; Mediation; Instruments; Humans; Knowledge based systems; Collaborative work; Collaboration; Software